Spinoza on human freedom reason, autonomy and the good life - Kisner, Matthew J., 1974- (Cambridge University Press, 2011)
"Spinoza was one of the most influential figures of the Enlightenment, but his often obscure metaphysics makes it difficult to understand the ultimate message of his philosophy. Although he regarded freedom as the fundamental goal of his ethics and politics, his theory of freedom has not received sustained, comprehensive treatment. Spinoza holds that we attain freedom by governing ourselves according to practical principles, which express many of our deepest moral commitments. Matthew J. Kisner focuses on this theory and presents an alternative picture of the ethical project driving Spinoza's philosophical system. His study of the neglected practical philosophy provides an accessible and concrete picture of what it means to live as Spinoza's ethics envisioned"--